Statistical properties of the least squares estimator of maximum excreted drug amount - Prodanova, Krasimira (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1996)
Inaccuracy in estimation of the maximum excreted drug amount ($U^{∞}$) is the main cause of errors in determination of some pharmacokinetic parameters of drugs. Usually, one estimates $U^{∞}$ using observed values of the cummulative excretion ($U(t)$). This paper uses a new stochastic model to obtain the least squares estimator of $U^{∞}$. The advantages of the model are that it is applicable for any drug, whose pharmacokinetics may be formalized with a linear $n$-compartment model ($n=1,2,3,...$) with or without phase of absorption and it may be used when the measurements for $U(t)$ are non-equidistant.